Cultivation of Entrepreneurial Talents Through Virtual Entrepreneurship Practice in Higher Education Institutions - An, Hengjie; Xu, Yuanyuan (Frontiers in Psychology, 2021)
The purpose is to study the influence of virtual entrepreneurship practice on entrepreneurial talent cultivation and innovation and entrepreneurship education in higher education institutions. First, a questionnaire is designed from three aspects: entrepreneurial awareness, entrepreneurial psychological quality, and entrepreneurial knowledge structure. Afterward, the questionnaire is issued to 200 students from a college in Shaanxi province, and SPSS 25 is chosen to analyze and characterize the virtual entrepreneurship practice education and the innovation and entrepreneurship education in higher education institutions. The results show that among all the subjects, nearly 20% of them do not understand entrepreneurship, nearly 85% of them concern about the risk of entrepreneurship, and nearly 70% of them take a negative attitude towards entrepreneurial failure. Meanwhile, the subjects have not formed an independent view on entrepreneurship, the subjects’ basic entrepreneurial quality is poor, their entrepreneurship awareness is weak, and their entrepreneurial psychological quality is poor. The subjects lack entrepreneurial quality rather than entrepreneurial knowledge. Finally, some suggestions are put forward on education on virtual entrepreneurship practice in higher education institutions from four aspects: improving the external environment of entrepreneurship, improving the entrepreneurship curriculum in higher education institutions, improving the teaching staff, and developing the practice bases for entrepreneurship education. The results provide some ideas about promoting the comprehensive reform of talent training mode in higher education institutions.